Formulation and Activity Testing of a Preparation of Cherry Fruit (Muntingia calabura L.) Syrup as Acute Antidiarrhea in Mice - Musfirah, Widya Suci; Rahim, Abdul; Fachreza, Homely; Ani, Karmelita; Syahira, Syifa (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2480, 2023)
The problem of diarrhea is an important problem to overcome, especially in the Samarinda area, East Kalimantan Province. The number of diarrhea cases is increasing every year. In 2021, there were 34,436 cases nationally and 4,706 cases in Samarinda. Viruses and bacteria can cause diarrhea. The cherry plant has antibacterial and antidiarrheal properties because of its Alkaloid, flavonoid and tannin content. This research focuses on investigating the potential of syrup from the secondary metabolite juice of cherry fruit syrup in curing acute diarrhea in male Wistar rats. The research method used was to compare 5 groups with varying concentrations of cherry syrup. Measurements include assessing when the diarrhea started, how often the diarrhea occurs, its texture, severity, and how long the diarrhea lasts. Research shows that cherry syrup has a positive effect in reducing diarrhea symptoms such as bowel movement frequency, consistency, weight and duration. Based on the results of research conducted, it shows that cherry fruit syrup ( Muntigia calabura L.) can treat acute diarrhea.